2003
DOI: 10.1016/s0378-1097(03)00296-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of the species of theBacteroides fragilisgroup by multiplex PCR assays using group- and species-specific primers

Abstract: We report a rapid and reliable two-step multiplex polymerase chain reaction (PCR) assay to identify the 10 Bacteroides fragilis group species^Bacteroides caccae, B. distasonis, B. eggerthii, B. fragilis, B. merdae, B. ovatus, B. stercoris, B. thetaiotaomicron, B. uniformis and B. vulgatus. These 10 species were first divided into three subgroups by multiplex PCR-G, followed by three multiplex PCR assays with three species-specific primer mixtures for identification to the species level. The primers were design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 26 publications
0
59
0
1
Order By: Relevance
“…1 Furthermore, patients with bowel inflammation, but not controls, have been observed to have high concentrations of mucosal bacteria (exceeding 10 9 /mL) and a dense, adherent mucosal biofilm mass composed predominantly of B. fragilis group organisms. 14,15 The B. fragilis group consists of at least 10 distinct species of organisms 20 and subspeciation of the adherent B. fragilis group organisms in the mucosal biofilm mass has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Furthermore, patients with bowel inflammation, but not controls, have been observed to have high concentrations of mucosal bacteria (exceeding 10 9 /mL) and a dense, adherent mucosal biofilm mass composed predominantly of B. fragilis group organisms. 14,15 The B. fragilis group consists of at least 10 distinct species of organisms 20 and subspeciation of the adherent B. fragilis group organisms in the mucosal biofilm mass has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides species-specific primer pairs were developed to amplify the 16S rRNA intergenic spacer region (ISR) as previously described. 20 One of these forward primers, 1392A (5′-GTACACACCGCCCGT) was combined with a reverse primer of our own design, Bfra-Rev20 (5′-AATTTAGAACCAATGAACG) to specifically amplify a 190-bp region of the B. fragilis ISR. A primer pair was also designed to generate amplicons of the B. fragilis enterotoxin (BFT) produced by ETBF, yielding a 109-bp fragment [BFT-F1 (5′-GAAAGTCAGACACGTGCAG-TACC) and BFT-R1 (5′-CCTGCATCTGGGCACTAAC)].…”
Section: Fecal Analysismentioning
confidence: 99%
“…One report developed group-specific primers to the ␤-isopropylmalate de-hydrogenase gene leuB and found that this was a useful tool for rapid diagnosis of Bacteroides infections (159). Our laboratory developed a multiplex PCR system with group-and speciesspecific primers to rapidly identify species of the B. fragilis group (146). Using the latter technique, 10 species of the B. fragilis group could be identified.…”
Section: Isolation and Identificationmentioning
confidence: 99%
“…The taxonomy of Bacteroides has undergone major revisions in the last few decades (see "Taxonomy" below), but the genus is now limited to species within the Bacteroides fragilis group, which now number Ͼ20. Names of species within the Bacteroides or Parabacteroides group to date are listed in Table 1 (146). Many of these species were isolated as single strains from human feces.…”
Section: Introductionmentioning
confidence: 99%
“…Several genera, Bacteroides, Acinetobacter, Flavobacterium, Chryseobacterium and Porphyrobacter, were identified in crab guts, and some species belonging to these genera ordinarily are related to some disease. For example, some Bacteroides species are opportunistic pathogens owing to their association with a variety of soft tissue and other infections (Liu et al, 2003). In shrimp, the intestinal microbial diversity investigated by molecular-dependent methods have revealed that the predominant bacterial population in the intestine of Chinese shrimp, Fenneropenaeus chinensis were Proteobacteria and Vibrio sp.…”
Section: Discussionmentioning
confidence: 99%